Case Report: Fecal microbiota transplantation via capsules ameliorated clinical outcomes in a patient with multiple sclerosis - Bibbò, Stefano; De Maio, Flavio; Capone, Fioravante; Quaranta, Gianluca; Rondinella, Debora; Rosato, Roberto; Minelli, Mauro; De Lorenzis, Desy; Sanguinetti, Maurizio; Cammarota, Giovanni; Di Lazzaro, Vincenzo; Masucci, Luca (Frontiers in Immunology, 2025)
Multiple Sclerosis (MS) has long been recognized as a multifactorial disease, associated with both genetic and enviromental factors. Its link to inflammatory processes has led to significant advances in understanding the immunological and neurobiological mechanisms underlying the disease. The presumed autoimmune etiology is currently guiding the development of therapeutic protocols in this direction. The intestinal bacteria population, known as Gut Microbiota (GM), plays a well-documented role in autoimmune and inflammatory diseases. Gut microbiota dysbiosis is associated in patients affected by MS. Fecal Microbiota Transplantation (FMT) is emerging as a potential strategy to restore eubiosis and modulate systemic inflammation. We treated a 42-year-old woman with severe MS disability by FMT via colonoscopic infusion followed by a 3-month treatment of daily oral capsules, containing frozen microbiota, in order to resolve gastrointestinal symptoms. Clinical follow-up was conducted at 30, 60, and 90 days. Microbiota profiling (16S rRNA sequencing) and intestinal permeability testing were performed at several time points before and post infusion. Post-FMT, gastrointestinal symptoms improved significantly, as well as in limb spasticity, trunk stability, and fine motor skills. Microbiota analysis revealed a marked reduction in the abundance of Akkermansia muciniphila (22.5% vs 6.6%). At phylum level, Actinomycetota remained elevated (22%), while Bacteroidota consistently showed low abundance (14%). The most favorable microbiota profile was observed at 90 days, which coincided with the peak of clinical improvement. Intestinal permeability also improved over time, despite the patient’s microbiota profile remaining distinct from the donor. This is the first report about combined FMT in MS. The procedure was safe, well tolerated, and associated with both gastrointestinal and neurological improvements. These findings support further exploration of FMT as a therapeutic adjunct in MS through controlled clinical trials.